2006
DOI: 10.2147/tcrm.2006.2.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pruritic diseases with topical calcineurin inhibitors

Abstract: The introduction of topical calcineurin inhibitors resulted in a significant improvement in the treatment of atopic dermatitis. In addition, rapid amelioration of pruritus could be observed. In case reports, other pruritic dermatoses such as chronic irritative hand dermatitis, rosacea, graft-versus-host-disease, and lichen sclerosus were also treated successfully with pimecrolimus and tacrolimus. Twenty patients were treated with tacrolimus and pimecrolimus in a surveillance study to evaluate efficacy in pruri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 24 publications
0
38
0
3
Order By: Relevance
“…In addition, they may also be beneficial treatments for pruritus associated with contact dermatitis and SD [135]. Side effects include burning and stinging sensations.…”
Section: Topical Treatmentsmentioning
confidence: 99%
“…In addition, they may also be beneficial treatments for pruritus associated with contact dermatitis and SD [135]. Side effects include burning and stinging sensations.…”
Section: Topical Treatmentsmentioning
confidence: 99%
“…The development of the topical calcineurin inhibitor pimecrolimus has led to considerable improvement in the treatment of atopic dermatitis [4], and there was a marked amelioration of pruritus as well [4,5,6]. There are also case reports on the antipruritic efficacy of pimecrolimus treatment in a series of itchy dermatoses (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There are also case reports on the antipruritic efficacy of pimecrolimus treatment in a series of itchy dermatoses (e.g. chronic irritative hand dermatitis, lichen sclerosus), including PN [6,7]. Pimecrolimus and tacrolimus are assumed to have, like capsaicin, an antipruritic effect by virtue of their influence on sensory cutaneous neurons and the phosphorylation of transient receptor potential subtype vanilloid 1 (TRPV1) receptor [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that TCIs can be successful in treating graft-versus-host disease, lichen planus, lichen sclerosis and prurigo nodularis (Ständer et al 2006b). The mechanism of action of these agents in reducing itch is unclear and possibly multifactorial.…”
Section: Topical Calcineurin Inhibitorsmentioning
confidence: 99%